Heartless : a pretty little liars novel - Shepard, Sara, 1977- (New York : HarperTeen, 2010)
Hanna, Aria, Emily, and Spencer have been telling some outrageous stories, but no one seems to believe them, so when a killer comes after them, they wonder if the town of Rosewood will believe them.
Young Adult
Keywords: Conduct of life -- Juvenile fiction; Friendship -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Secrecy -- Juvenile fiction; Conduct of life -- Fiction; Friendship -- Fiction; High schools -- Fiction; Mystery and detective stories; Schools -- Fiction; Secrets -- Fiction; Conduct of life -- Fiction; Friendship -- Fiction; High schools -- Fiction; Mystery fiction; School stories; Secrecy -- Fiction; Mystery fiction